Characteristics and performance of aerobic granulation seeded with anaerobic bioflocs for treatment of domestic wastewater. Issue 1 (June 2020) - Purba, L D A; Abdullah, N; Yuzir, A; Halim, M H Ab
Abstract: In the present study, aerobic granular sludge was developed using a combination of anaerobic bioflocs and activated sludge. The granulation process and removals of organic compound (COD and ammoniacal nitrogen) were observed for 140 days of experimental period. The granulation process occurred after 30 days of the experiments, indicated by the decrease in sludge volume index (SVI) and increase of biomass concentration. The COD and ammoniacal nitrogen removal efficiencies were 67% and 72%, respectively. Mature aerobic granules were developed with diameter ranging from 4 to 6 mm with excellent settling velocity at 75 m/h. The results indicated the possibility to use anaerobic bioflocs as seeding to develop aerobic granular sludge for domestic wastewater treatment.